PERAN PERPUSTAKAAN SLB DALAM MENINGKATKAN PENGELOLAN PERPUSTAKAAN SESUAI STANDAR NASIONAL PERPUSTAKAAN (SNP) : : STUDI ANALISIS PERPUSTAKAAN SLB ANAK MANDIRI SERANG, PROVINSI BANTEN DAN PERPUSTAKAAN SLB BINA ANAK BANGSA KOTA PONTIANAK, PROVINSI KALIMANTAN BARAT - Tinna Noviyanti (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2024)
(Title "The Role of the SLB Library in Improving Library Management in Accordance with National Library Standards (SNP): Analysis Study of the Serang Mandiri Children's SLB Library, Banten Province and the Bina Anak Bangsa SLB Library, Pontianak City, West Kalimantan Province".) The aim of this research is to increase knowledge regarding 9 aspects of organizing, managing and developing SLB libraries in accordance with National Standards, as well as to motivate all elements of library management, including school principals, library heads and library management staff in managing and developing their libraries to be even better and also more useful for the user. This research uses a descriptive qualitative research design. The subjects in this research were school principals, library staff, and teachers as teaching staff. The techniques used in data collection are observation, interviews, and documentation with data analysis techniques. The results of this research are the role of libraries in improving library management according to the National Library Standards in the Serang Mandiri Children's SLB Library, Banten Province and the Bina Anak Bangsa SLB Library in Pontianak City, West Kalimantan Province which have not been managed optimally for 9 aspects of library standards, namely from the library collection aspect, facilities and infrastructure, library services, library administration, library management, However, in the aspect of developing innovation and increasing the love of reading, the Serang Mandiri Children's SLB Library, Banten Province and the Bina Anak Bangsa SLB Library, Pontianak City, West Kalimantan Province have organized and developed it with various activities innovative and creative. Meanwhile, the ratio aspect of the development index can be stated that the ratio of the number of library members at the Serang Mandiri Children SLB Library, Banten Province to the availability of printed books is 1:2 and at the Bina Anak Bangsa SLB Library, Pontianak City, West Kalimantan Province, namely 1:1. library for all library members in both libraries is not yet fulfilled; while equal access to library services for users at all levels and classes; and the number of library activities involving users has been fulfilled.